Implementasi Nilai-Nilai Kebangsaaan Berbasis UUD 1945,Dalam Penerapan Tantangan Regulasi Dan Persoalan Dalam Industri Migas Indonesia - Edy Soesanto; Amelia Novianti; Ani Handayani (International Forum of Researchers and Lecturers, 2024)
This journal reviews the implementation of national values based on the 1945 Constitution in facing regulatory challenges and problems in the Indonesian oil and gas industry. This research explores how the national values reflected in the 1945 Constitution can be applied in the complex context of the oil and gas industry. The analysis results show that the Indonesian oil and gas industry is faced with various challenges, including complex regulations and suboptimal governance issues. However, implementing national values in oil and gas industry regulations can strengthen the country's energy sovereignty. Steps to increase the implementation of these values include improving regulations that are oriented towards national interests, increasing transparent governance, and a commitment to protecting the environment and surrounding communities. This journal highlights the importance of cooperation between government, industry and society in achieving these goals. The results of the analysis show that the implementation of national values in the Indonesian oil and gas industry is faced with several challenges, such as complex regulations, suboptimal governance, and environmental and social issues that must be addressed. To overcome these challenges, efforts are needed to strengthen the implementation of national values in oil and gas industry regulations, such as improving regulations that are more oriented towards national interests, increasing transparent and accountable governance, and strengthening commitment to efforts to protect the environment and surrounding communities.